2014
DOI: 10.1155/2014/307942
|View full text |Cite
|
Sign up to set email alerts
|

Serum Inter-Alpha-Trypsin Inhibitor Heavy Chain 4 (ITIH4) in Children with Chronic Hepatitis C: Relation to Liver Fibrosis and Viremia

Abstract: Liver fibrosis and viremia are determinant factors for the treatment policy and its outcome in chronic hepatitis C virus (HCV) infection. We aimed to investigate serum level of inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4) and its relation to liver fibrosis and viremia in children with chronic HCV. ITIH4 was measured by ELISA in 33 treatment-naive children with proved chronic HCV and compared according to different clinical, laboratory and histopathological parameters. Liver histopathological changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…Research by other authors shows that ITIH4 may also have potential antiviral properties against chronic hepatitis C virus. Sira et al (2014) found that hepatitis C viremia was lower in patients with higher serum ITIH4 levels. Previous studies indicate that ITIH4 play a particularly important role not only in inflammation but also in carcinogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…Research by other authors shows that ITIH4 may also have potential antiviral properties against chronic hepatitis C virus. Sira et al (2014) found that hepatitis C viremia was lower in patients with higher serum ITIH4 levels. Previous studies indicate that ITIH4 play a particularly important role not only in inflammation but also in carcinogenesis.…”
Section: Discussionmentioning
confidence: 94%
“…We are constantly searching for new, more specific markers of liver fibrosis. A single study conducted in CHC children tested the significance of markers such as the C4a Complement[ 70 ] and inter-alpha-trypsin inhibitor heavy chain 4 (ITIH4)[ 71 ], which was not associated with liver fibrosis scores but could predict significant fibrosis. The results of a recent study indicated that the non-invasive biomarkers APRI, FIB-4 and AST modified by the body mass index z-score have a good to excellent performance for detecting significant liver fibrosis[ 72 ].…”
Section: Serum Biomarker Testsmentioning
confidence: 99%
“…We have previously studied other serological non-invasive markers such as serum complement C4a [35] and serum interalpha-trypsin inhibitor heavy chain 4 [36] in children with chronic HCV. It can be concluded that none of these markers alone can reach an accurate prediction of liver fi brosis.…”
Section: Ykl-40 Is An Emerging New Infl Ammation Biomarkermentioning
confidence: 99%